Piet Mondrian's Neo-Plastic artworks (1917-1944) through the lens of Zen Buddhism - Fallahzadeh, Ali; Gamache, Geneviève (University of Malaya, 2017)
This paper firstly proposes a paralleled visual analysis of Piet Mondrian’s (1872-1944) selected Neo-Plastic artworks with his essays pertinent to the role of “pure intuition” in Neo-Plasticism doctrine.The result of this chronological visual-textual analysis is further reinterpreted through the metaphysical lens of Zen discourse in the 20th century chiefly discussed by scholars like Nishida Kitaro regarding to the Zen notions eternal now, mojou (impermanence), mu (nothingness), and śūnyatā (ultimate truth/emptiness). Ultimately this paper will illuminate the degree of kinship between the steady development of Mondrian’s artistic thought in three phases of his artistic career, written in conjunction with the creation of his Neo-Plastic art, and central premises of Zen Buddhism.